The Influence of Tax Rates, Tax Knowledge, Criminal Sanction, Information Technology Against Tax Evasion Behavior in KPP Pratama Makassar Selatan - Fidhia Desiyanti Sabara (STIM LASHARAN JAYA MAKASSAR, 2018)
The aims of this research are :(1) To know the effect of tax rate onthe behavior of tax evasion;(2) To know the effect of the knowledge of Taxation on the behavior of tax evasion; (3) To know the effect of Criminal Sanctions on tax evasion behavior; (4) To know the effect of information technology on tax evasion behavior. The method of analysis used is multiple linear regression. With a sample of 98 taxpayers in KPP Pratama Makassar Selatan. The results of this research show that : (1) tax rates have a positive and significant effect on tax evasion behavior in KPP Pratama Makassar Selatan; (2) knowledge of taxation have a positive and significant effect on tax evasion behavior; (3) criminal sanction have a positive and significant effect on tax evasion behavior; (4) Information technology have a positive and significant effect on tax evasion behavior